Check Point NG VPN-1/Firewall-1: Advanced Configuration and Troubleshooting - Noble, Jim (Syngress Publishing, 2011)
Check Point Software Technologies is the worldwide leader in securing the Internet. The company's Secure Virtual Network (SVN) architecture provides the infrastructure that enables secure and reliable Internet communications. Check Point recently announced a ground-breaking user interface that meets the industry's next generation Internet security requirements, including simplified security management for increasingly complex environments. Built upon Check Point's Secure Virtual Network (SVN) architecture, the Next Generation User Interface revolutionizes the way security administrators define and manage enterprise security by further integrating management functions into a security dashboard and creating a visual picture of security operations. The Next Generation User Interface delivers unparalleled ease-of-use, improved security and true end-to-end security management. Check Point's revenues have more than doubled in each of the last two years, while capturing over 50% of the VPN market and over 40% of the firewall market according to IDC Research. The explosive growth of the company is further evidenced by over 29,000 IT professionals becoming Check Point Certified so far. This book will be the complimentary to Syngress' best-selling Check Point Next Generation Security Administration, which was a foundation-level guide to installing and configuring Check Point NG. This book will assume that readers have already mastered the basic functions of the product and they now want to master the more advanced security and VPN features of the product. Written by a team of Check Point Certified Instructors (the most prestigious Check Point certification) this book will provide readers with a complete reference book to Check Point NG and advanced case studies that illustrate the most difficult to implement configurations. Although not a Study Guide, this book will cover all of the objectives on Check Point's CCSE Exam.